Assessment of digital competencies in higher education faculty: a multimodal approach within the framework of artificial intelligence - Moreira-Choez, Jenniffer Sobeida; Gómez Barzola, Ketty Elizabeth; Lamus de Rodríguez, Tibisay Milene; Sabando-García, Angel Ramón; Cruz Mendoza, Juan Carlos; Cedeño Barcia, Lizandro Agustín (Frontiers in Education, 2024)
Digital competencies are currently a fundamental pillar in the professional development of educators, especially in Higher Education contexts where the integration of educational technologies plays a crucial role in enhancing teaching and learning processes. This study focused on assessing the digital competencies of faculty at the Technical University of Manabí. A descriptive and non-experimental approach was utilized with a sample of 279 professors. Data were collected through a quantitative multimodal design using the Higher Education Digital Competencies Assessment Questionnaire (CDES), and subsequently analyzed using a structural equation model in AMOS software. The results indicated a significant correlation between the perceptions of faculty members and the evaluated dimensions, highlighting the need for adjustments in the model due to some discrepancies in the goodness-of-fit indices. The study emphasizes the importance of ongoing evaluation and optimization of the structural model to refine the integration of digital competencies, demonstrating the potential of these competencies to enrich teaching practices. It concludes that continuous validation and adjustment of the model are essential to align faculty perceptions with actual digital competencies.Changes made according to question 3 3-We thank the reviewer for pointing out this discrepancy. To clarify, the number 279 mentioned in the abstract indeed corresponds to the sample size used in the study. In the methodology section, the text will be adjusted to specify that the total population of the faculty at the Technical University of Manabí is larger, and a detailed calculation of how the sample size was determined from this total population will be provided.Changes made according to question 2 2-In the abstract, the reliability analysis of the instrument was removed, as this aspect is no longer an objective of the study, in accordance with the suggestion of Reviewer 1 in question 2.